2019
DOI: 10.1177/2515690x19865166
|View full text |Cite
|
Sign up to set email alerts
|

The Wound Healing Property of N-Methyl-(2S,4R)-trans-4-Hydroxy-L-Proline from Sideroxylon obtusifolium is Related to its Anti-Inflammatory and Antioxidant Actions

Abstract: Wound healing involves the interaction of blood cells, proteins, proteases, growth factors, and extracellular matrix components. Inflammation is one of the first events occurring during this process. Previously, we showed that the N-Methyl-(2S,4R)-trans-4-Hydroxy-L-Proline (NMP) from Sideroxylon obtusifolium leaves (a Brazilian medicinal species) presents an anti-inflammatory action. Considering inflammation as an important event in the wound healing process, the objectives were to investigate the topical effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 44 publications
2
14
0
1
Order By: Relevance
“…The occurrence of compound I was confirmed by the MS analysis, in full agreement with the literature [17,18,35]. The compound has been previously reported in Sideroxylon obtusifolium (Sapoteaceae), a medicinal species from Northeast Brazil with anti-inflammatory [36] and wound healing properties [37]. The authors reported that the compound at doses ranging from 25-100 mg/kg decreased licking time and paw edema in the formalin test, as well as a complete reversion of the increased number of polymorphonuclear cells in the inflammation point.…”
Section: Amino Acids and Derivativessupporting
confidence: 87%
“…The occurrence of compound I was confirmed by the MS analysis, in full agreement with the literature [17,18,35]. The compound has been previously reported in Sideroxylon obtusifolium (Sapoteaceae), a medicinal species from Northeast Brazil with anti-inflammatory [36] and wound healing properties [37]. The authors reported that the compound at doses ranging from 25-100 mg/kg decreased licking time and paw edema in the formalin test, as well as a complete reversion of the increased number of polymorphonuclear cells in the inflammation point.…”
Section: Amino Acids and Derivativessupporting
confidence: 87%
“…Similarly, a phytomodulatory hydrogel with hemicelluloses extracted from seeds of Caesalpinia pulcherrima (Fabaceae) and mixed with phytomodulatory proteins obtained from the latex of Calotropis procera, enhanced the healing effects by high collagen deposition and modulating some aspects of the inflammatory phase (Vasconcelos et al, 2018). Corroborating with this data, it was discovered that the methanol fraction of quixaba leaves (MFSOL), contains as a main component, the NMP, a derivative from L-proline (amino acid precursor of collagen), that showed cicatrizant effect in the topical treatment of induced excisional lesions in mice, through modulation of the inflammatory response, and increase of the antioxidant response and stimulation of the production of collagen fibers (Aquino et al, 2019). Also, a study with the ethanol extract of the leaves of Passiflora edulis reproduced an acceleration the repair, to reduce the number of inflammatory cells on the 7th day of treatment and to increase the number of fibroblasts and the deposition and organization of the fibers of collagen in 14 days of repair of burns in mice (Barros, Santos, Coelho, Reis, & Bezerra, 2016).…”
Section: Discussionmentioning
confidence: 91%
“…Other study demonstrated antinociceptive and anti-inflammatory properties of L-proline, N-methyl-(2S, 4R)-trans-4-hydroxy-L-proline (NMP), presents in major proportion in the methanol fraction of leaves of S. obtusifolium (MFSOL) (Aquino et al, 2017). Also, NMP showed wound healing activity on excisional wounds, which was related to its anti-inflammatory and antioxidant actions (Aquino et al, 2019). However, there is no knowledge of whether methanol fraction MFSOL is the healing process in wounds caused by burns.…”
Section: Introductionmentioning
confidence: 99%
“…Penn. belongs to the Sapotaceae family and is a medicinal plant used in Brazil due to its analgesic and anti-inflammatory activities, as already demonstrated by us [7,8] and others [9]. Furthermore, experimental and clinical evidence indicates that there is a close relationship between epileptogenesis and brain inflammation.…”
Section: Introductionmentioning
confidence: 84%
“…a DG: (a) vs. control, p < 0.001; (b) vs. Pilo + NMP100, p < 0.001; (c) vs.Pilo + NMP200, p < 0.01; (d) vs. control, p < 0.05. b tC: (a) vs. control, p < 0.0001; (b) vs. Pilo + NMP100, p < 0.0001; (c) vs. Pilo + NMP200, p < 0.0001. c CA1: (a) vs. control, p < 0.001; (b) vs. Pilo + NMP100, p < 0.001; (c) vs. Pilo + NMP200, p < 0.001; (d) vs. control, p < 0.05. d CA3: (a) vs. control, p < 0.001; (b) vs. Pilo + NMP100, p < 0.001; (c) vs. Pilo + NMP200, p < 0.001. (one-way ANOVA and Tukey multiple comparison test).Plant material and preparation of the methanol fraction containing the bioactive constituent N-methyl-(2S,4R)-trans-4-hydroxy-L-proline S. obtusifolium leaves were collected and handled as previously described[8] and identified (voucher specimen #10,648) by Maria Arlene Pessoa da Silva, Ph.D., botanist at the Herbarium "Dárdano de Andrade Lima", Regional University of Cariri (URCA), Crato, Brazil.…”
mentioning
confidence: 99%